Antioxidants 2019
DOI: 10.5772/intechopen.85568
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endogenous Antioxidants in the Treatment of Experimental Arthritis

Abstract: The pathogenesis of rheumatoid arthritis is poorly understood; however, elevated oxidative stress has been described to be involved. In this chapter, we present experiments with endogenous molecules bearing antioxidative properties. In our studies, we used male Lewis rats, and the arthritis was induced with Mycobacterium butyricum. In the first experiment, we tested coenzyme Q 10 (CoQ 10) in the oral daily dose of 100 mg/kg b.w. Markers of inflammation and total antioxidant status were corrected in the group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Ubiquinol treatment had no effect on tocopherols concentration in PLT; they were reduced in both groups near controls. Recently we found elevated concentrations of γT in plasma and skeletal muscle tissue of arthritic rats together with increased markers of infl ammation (39), and treatment with CoQ 10 corrected the increased γT concentration and improved the mitochondrial function (40).…”
Section: U N C O R R E C T E Dmentioning
confidence: 95%
“…Ubiquinol treatment had no effect on tocopherols concentration in PLT; they were reduced in both groups near controls. Recently we found elevated concentrations of γT in plasma and skeletal muscle tissue of arthritic rats together with increased markers of infl ammation (39), and treatment with CoQ 10 corrected the increased γT concentration and improved the mitochondrial function (40).…”
Section: U N C O R R E C T E Dmentioning
confidence: 95%
“… Structures of active metabolites of mushroom: (A) Tocopherol ( Bauerova et al, 2019 ) (B) Carotenoid ( Eldahshan and Singab, 2013 ). …”
Section: Introductionmentioning
confidence: 99%
“…An essential component of the mitochondrial respiratory chain for energy production is coenzyme Q 10 (CoQ 10 ) which also has antioxidant properties. Our previous study on the rat model of rheumatoid arthritis (adjuvant-induced arthritis) showed reduced mitochondrial oxidative phosphorylation in myocardial and skeletal muscle [ 20 ], increased markers of inflammation and decreased concentrations of coenzyme Q 9-OX in skeletal muscle tissue and mitochondria [ 21 ].…”
Section: Introductionmentioning
confidence: 99%